Intelligent automated system based on a fuzzy logic system for plant protection product control in orchards - Berk, P; Belšak, A; Stajnko, D; Lakota, M; Muškinja, N; Hočevar, M; Rakun, J (International Journal of Agricultural and Biological Engineering, 2019)
The spraying of plant protection product (PPP) in orchards is a very hazardous working procedure, owing to the spray drift caused by the uneven operation of conventional axial boom sprayers. This research describes an intelligent automated system for precise (PPP) distribution in real-time. It is based on an intelligent decision-making model using ultrasonic measurements of leaf area density under laboratory conditions, which serve to trigger electromagnetic valves (EMV) on the axial boom sprayer. A fuzzy logic algorithm was an integrated part of the intelligent system for controlling the PPP by generating the pulse width modulation signal and applying it through the EMV of the prototype boom sprayer. The results showed that by using an intelligent decision-making model, the same efficiency as with conventional methods could be achieved, but with reduced usage of plant protection products. Thus, the intelligent automated system used 4.8 times less spray mixture than the conventional one. Keywords: plant protection product, boom sprayer, electromagnetic valve, fuzzy logic algorithm, tree canopy DOI: 10.25165/j.ijabe.20191203.4476 Citation: Berk P, Belšak A, Stajnko D, Lakota M, Muškinja N, Hočevar M, et al. Intelligent automated system based on a fuzzy logic system for plant protection product control in orchards. Int J Agric & Biol Eng, 2019; 12(3): 92–102.